Possible Treatment Approaches of Sulfur Mustard-Induced Lung Disorders, Experimental and Clinical Evidence, an Updated Review - Khazdair, Mohammad Reza; Boskabady, Mohammad Hossein (Frontiers in Medicine, 2022)
Sulfur mustard (SM) is one of the major potent chemical warfare that caused the death of victims in World War I and the Iraq-Iran conflict (1980–1988). The respiratory system is the main target of SM exposure and there are no definitive therapeutic modalities for SM-induced lung injury. The effects of the new pharmaceutical drugs on lung injury induced by SM exposure were summarized in this review. Literature review on PubMed, ScienceDirect, and Google Scholar databases was performed to find papers that reported new treatment approach on SM-exposure-induced injury in the respiratory system until October 2019. The search was restricted to sulfur mustard AND induced injury (in vitro studies, animal experiments, and clinical trials) AND respiratory system OR lung, AND treatment in all fields. Two hundred and eighty-three relevant articles were identified that 97 retrieved articles were eligible and were included in the review. Some new pharmaceutical drugs have shown therapeutic potential in controlling various characteristics of lung injury due to SM exposure. Recent studies showed therapeutic effects of mucolytic drugs, non-steroidal drugs, and antibiotics on reducing lung inflammation, oxidative stress responses, and modulating of the immune system as well as improving of respiratory symptoms and pulmonary function tests. Studies on the therapeutic effects of new agents with amelioration or treatment of SM-induced lung injury were reviewed and discussed.